Fascioliasis in vicugna (Vicugna vicugna) in the central highlands of Peru - Samamé A., Luis Miguel (2016)
The aim of this study was to determine the presence of F. hepatica eggs in vicugnas in the Paccha area, Junín, Peru, and to evaluate its association with sex and age. Samples (n=143) were collected from the rectum during a «chaccu» activity (annual capture of wild vicugnas by the local peasants for shearing (September). Samples were analyzed by the rapid sedimentation technique and the determination of parasite load – eggs per gram of feces (epg) – by the McMaster method. The frequency of F. hepatica was 32.